Enamel Hypoplasia In Canine Distemper Recovered Pup : A Case Report - Vijayanand, V; Shoman, M Shiju; Methai, A; Kavitha, S; Sathimoorthy, T (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A seven month old, male, non descript pup was brought to Veterinary University Peripheral Hospital, Madhavaram Milk Colony, Chennai with the primary complaint of non-eruption of permanent teeth following the fall of milk teeth. Examination of oral cavity revealed absence of teeth (incisors, canine, molar and premolars) in both the jaws and the entire dental pad appeared smooth. The dog appeared lean with the tongue protruded (about 2 inches) out of oral cavity on the right side. History revealed that about two months earlier the dog had a recovery from an exposure to Canine Distemper virus. Radiograph